2012
DOI: 10.1002/cssc.201200416
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Reduction of Acetone in a Proton‐Exchange‐Membrane Reactor: A Model Reaction for the Electrocatalytic Reduction of Biomass

Abstract: Acetone was electrocatalytically reduced to isopropanol in a proton-exchange-membrane (PEM) reactor on an unsupported platinum cathode. Protons needed for the reduction were produced on the unsupported Pt-Ru anode from either hydrogen gas or electrolysis of water. The current efficiency (the ratio of current contributing to the desired chemical reaction to the overall current) and reaction rate for acetone conversion increased with increasing temperature or applied voltage for the electrocatalytic acetone/wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 68 publications
3
74
2
1
Order By: Relevance
“…The electrochemical hydrogenation of acetone dissolved in water and cyclohexane in a polymer electrolyte reactor showed that hydrogen evolution was a competing reaction with a similar reaction rate [192]. In a cell with a PtRu catalyst and a Nafion® 117 PEM, a maximum rate and current efficiency was achieved at an acetone concentration of about 3.5 M [193]. Increasing the cell temperature increases the reaction rate and current efficiency (up to about 60%) [193].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical hydrogenation of acetone dissolved in water and cyclohexane in a polymer electrolyte reactor showed that hydrogen evolution was a competing reaction with a similar reaction rate [192]. In a cell with a PtRu catalyst and a Nafion® 117 PEM, a maximum rate and current efficiency was achieved at an acetone concentration of about 3.5 M [193]. Increasing the cell temperature increases the reaction rate and current efficiency (up to about 60%) [193].…”
Section: Reviewmentioning
confidence: 99%
“…In a cell with a PtRu catalyst and a Nafion® 117 PEM, a maximum rate and current efficiency was achieved at an acetone concentration of about 3.5 M [193]. Increasing the cell temperature increases the reaction rate and current efficiency (up to about 60%) [193]. …”
Section: Reviewmentioning
confidence: 99%
“…[12,18,19] Electrochemical hydrogenation has been demonstrated for multiple industrial reactions (e. g., nitrobenzene to azobenzene, naphthalene to 1,4-dihydronaphthalene [20,21] ) and can improve selectivity and rate over thermochemical hydrogenation. [8,9,12,[16][17][18][22][23][24][25][26][27][28][29] Additionally, electrochemical processes can exhibit fewer environmental impacts than thermochemical processes by utilizing electricity generated from renewable energy resources. As of 2017, 80 % of energy consumed by U.S. industrial production comes from petroleum, natural gas, and coal-all of which emit a total of 964 million metric tons of carbon dioxide annually.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol is a valuable byproduct in the production of biodiesel and fatty acids . Recently, efforts have been devoted to developing efficient electrochemical conversion technologies to produce value‐added chemicals and/or energy from biomass‐derived oxygenates such as glycerol . The electrocatalytic conversion process of glycerol is a promising technology that can produce valuable chemicals such as dihydroxyacetone, glyceraldehyde, and glyceric acid by selective oxidation reaction and electrical energy by a full oxidization reaction .…”
Section: Introductionmentioning
confidence: 99%